Dari Kekuasaan dan Seksualitas: Homofobia sebagai Konstruksi Sosial dalam Perspektif Foucault: Power and Sexuality: Homophobia as a Social Construction in Foucault's Perspective - Bethari, Ratri Ayu (Undiksha, 2024)
Homophobia is often regarded as a normal response to homosexuality, which deviates from social and religious norms. The term was first coined by psychologist George Weinberg in his book Society and the Healthy Homosexual (1972) to describe prejudice, fear, and rejection towards homosexual individuals. This research aims to understand that views on homosexuality are not natural but influenced by norms and values constructed through Michel Foucault's theory of discourse. The focus of this study is how homophobia, from Foucault's perspective, emerges as a discourse created by power to control society. The research method employed is a literature study with a hermeneutic approach to analyze texts related to Foucault's thoughts and homophobia. The findings indicate that power, according to Foucault, is pervasive and not centralized. Discourse, as a result of the dissemination of knowledge by power, plays a role in shaping society's perception of homosexuality. This discourse creates categories of normal and abnormal sexuality, with homosexuality being considered deviant. The study concludes that homophobia is a social construct formed by the discourse of power to maintain control over society, and that negative views towards homosexuality are based on norms and values produced by power through discourse